Craving, cortisol and behavioral alcohol motivation responses to stress and alcohol cue contexts and discrete cues in binge and non‐binge drinkers. (9th August 2018) - Blaine, Sara K.; Nautiyal, Nisheet; Hart, Rachel; Guarnaccia, J.B.; Sinha, Rajita
Abstract: Alcohol use disorders are associated with high craving and disruption of stress biology, but their role in behavioral alcohol motivation is less clear. We examined the effects of craving and cortisol responses on behavioral alcohol motivation to stress, alcohol cue and neutral‐relaxing context cues, in addition to discrete alcohol cues, in demographically matched binge/heavy (BH) and moderate (MD) social drinkers. Subjects participated in a 3‐day laboratory experiment of provocation by three personalized guided imagery contexts and discrete alcohol cues followed by the 'alcohol taste test' (ATT) to assess behavioral motivation, as measured by ATT intake. Post‐ATT alcohol effects on craving and cortisol responses were also examined. Results indicate BH consumed significantly more alcohol than MD in the ATT. Stress and alcohol cue contexts, relative to neutral, led to significantly greater ATT intake across both groups, which also correlated positively with self‐reported alcohol use in past 30 days. Stress and alcohol context and discrete alcohol cues each significantly increased alcohol craving, more so in the BH than MD, and significantly predicted greater ATT intake in BH only. The BH showed significantly lower cortisol responses than MD overall and blunted cortisol responses to cues predicted significantly greater ATT intake in the stress condition for BH and in the alcohol cue condition for MD. Higher ATT intake predicted greater cortisol response and higher craving post‐ATT, and these effects were moderated by group status. In sum, findings suggest a role for sensitized context‐induced craving and blunted cortisol responses in increased behavioral motivation for alcohol. Abstract : Binge/heavy (BH) relative to moderate (MD) social drinkers consumed more in an alcohol taste test after exposure to neutral, alcohol cue and stress conditions. Greater alcohol craving, but blunted cortisol responses in the stress condition, each predicted more alcohol intake in the alcohol taste test for BH but not MD drinkers. Also, the greater the amount of alcohol consumed, the higher the cortisol response post‐alcohol intake in all participants. Craving and cortisol during stress modulates alcohol motivation in BH drinkers.